Effects of long term normobaric hyperoxia exposure on lipopolysaccharide-induced lung injury. (7th February 2020) - Ha, Jick Hwan; Kim, Sei Won; Kim, In Kyoung; Yeo, Chang Dong; Kang, Hyeon Hui; Lee, Sang Haak
Abstract: Purpose/Aim of the study: Prolonged exposure to hyperoxia can cause injury to normal lung tissue. However, patients with acute hypoxic respiratory failure are frequently exposed to very high oxygen levels. This study investigated the effects of long term normobaric hyperoxia exposure in a mouse model of acute severe lung injury (SLI). Meterials and Methods: C57BL/6J mice were injected intratracheally with lipopolysaccharide (LPS, 4 mg/kg) to induce acute lung injury. After 2 h, mice were divided into two groups, and then exposed to room air or hyperoxic conditions for 48 h. Animals in the hyperoxia group were placed within their cages in a Plexiglass chamber with an atmosphere of 95% O2 maintained constant using an oxygen analyzer. After exposure to normoxia (N) or hyperoxia (H) for 48 h, the left lungs were collected for tissue paraffin block or oxidative stress assay. One lobe of the right lung was collected for lung/body weight ratio. The lung injury score and the mean linear intercept were evaluated in hematoxylin and eosin -stained lungs. The biochemical tests were performed by using ELISA assay. Results: Lung injury scoring, lung/body weight, and mean linear intercept were not significantly different between the N + LPS (NLPS) and H + LPS (HLPS) groups. Similar trends were observed in hydroxyproline and transforming growth factor-β (TGF-β) levels. Total cell and neutrophil counts in bronchoalveolar lavage fluid showed no significant differences between NLPS and HLPS groups. Histological analyses demonstrated more severe lung injury and fibrosis in the NLPS group than in the HLPS group. In addition, interleukin (IL)-1β was significantly decreased in the HLPS group compared to the NLPS group. Other inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and IL-6, showed similar trends. The malondialdehyde (MDA) level was significantly lower in the HLPS group than in the NLPS group. Conclusions: Exposure to hyperoxia did not augment lung injury in the LPS-induced lung injury model, and some indicators even showed better outcomes. These results suggest that long-term high-oxygen therapy in patients with SLI has low risk of lung injury.